KONDISI EKSISTING ALIRAN SUNGAI CIBARUKRUK, CITARUM DAN CIBOGO DAN MENGHITUNG DEBIT SUNGAI DENGAN TEKNIK MENGUNAKAN CURRENT METER - Abellia Fanny Aldeta; Abdul Hadi Putra; Aditya Herfianda; Aditya Saputra; Apriadi Agussalim; Nurfadhilla Nurfadhilla; Nurul Rahmadilla Edgar; Randu Prayoga Putra; Shintia Franzela; Tasa Anike; Widya Prarikeslan; Aprizon Putra (JURNAL BUANA, 2020)
This research was conducted at three locations, Cibarukruk River, Citarum River and Cibogo River. Based on the background of this study aims to determine the geological conditions of the constituent rock at location surveyed, the river profile and river flow calculation techniques using current meters. By using the river flowrate calculation method. But when the authors conducted a field survey, the area surveyed was in the dry season so the three rivers could not be counted for river discharge. From this study, it was found that the Cibarukruk River has a U-shaped morphology located in the Alluvial region, which has soil constituent rocks and sedimentary rocks which form the average constituent rocks in the river area. This river has a length of A-B which is 10 cm, and width A is 4 m and width B is 6 m. Citarum River is located in Cisanti which is at the foot of Wayang Windu Mountain. Cisanti is one of upstream Citarum 0 Kilometers river. Citarum is an artificial river that has only soil constituent rocks. The Cibogo River is also in the Alluvial area which has a constituent rock in the form of sedimentary rock consisting of clay and sand. The length of this river is 9.8 meters and 6.2 meters wide. This river has the same morphology as the Cibarukruk river which has a cross-section in the shape of the letter U.